Dampak Keberadaan Pojok Baca Terhadap Perilaku siswa di Man 1 Blangkejeren - belangihumaira; Zubaidah; Suraiya (Pustabiblia: Journal of Library and Information Science, 2025)
The collection of diverse and quality literature available in the reading corner should ideally have a positive impact and help in the formation of student behavior and ethics. However, in the students of Madrasah Aliyah Negeri (MAN) 1 Blangkejeren, there are several problems of student behavior and ethics that cause concern among teachers and parents. For this reason, the purpose of this study was to determine the impact of the Reading Corner on the behavior of MAN 1 Blangkejeren students. This research was conducted using a qualitative approach with descriptive method. Data were obtained from interviews and observations. The results showed that the existence of the reading corner at MAN 1 Blangkejeren had a positive impact on changes in student behavior. The number of students at MAN 1 Blangkejeren is 170 students, of which there are 11 students who have problematic behavior, such as smoking, fighting, online gambling, and bringing marijuana to school. For these 11 students, there was a change in behavior. Thus, the reading corner of MAN 1 Blangkejeren has an impact on changes in student behavior. In accordance with Kurt Lewin's theory, that the provision of educational understanding by counseling teachers to students of various good / bad values available in the literature in the Steel Corner is a stimulus that has a positive impact on student responses, so that students can understand the good values that must be done and the bad values that must be avoided and eliminated in each student.